Molecular cloning, expression, and purification, along with in silico epitope analysis of recombinant enolase proteins (a potential vaccine candidate) from Candida albicans and Candida auris - Shukla, Manisha; Singh, Rohit; Chandley, Pankaj; Rohatgi, Soma (Frontiers in Fungal Biology, 2024)
Candida albicans is the predominant cause of systemic candidiasis, although other non albicans Candida species are progressively becoming more widespread nowadays. Candida auris has emerged as a deadly multidrug-resistant fungal pathogen, posing a significant threat to global public health. In the absence of effective antifungal therapies, the development of a vaccine against C. auris infections is imperative. Enolase, a key glycolytic enzyme, has emerged as a promising vaccine candidate due to its immunogenic properties and essential role in fungal virulence. Herein, full-length Enolase gene sequences from C. albicans and C. auris were cloned into suitable expression vector and transformed into Escherichia coli expression hosts.Recombinant Enolase proteins were successfully expressed and purified using affinity chromatography under native conditions, followed by SDS-PAGE characterization and Western blot analysis. CD spectroscopy verified the existence of expressed proteins in soluble native conformation. Preliminary in silico studies verified the immunogenicity of recombinant Enolase proteins isolated from both C. albicans and C. auris. Furthermore, bioinformatics analysis revealed conserved B-cell and T-cell epitopes across C. albicans and C. auris Enolase proteins, suggesting potential cross-reactivity and broad-spectrum vaccine efficacy. Our findings are anticipated to play a role in advancing therapeutic as well as diagnostic strategies against systemic candidiasis.